2015
DOI: 10.5603/fm.2015.0111
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of maternal protein restriction on postnatal lung alveoli development of rat offspring

Abstract: Poor nutrition of women during pregnancy causes reduction in foetal growth (Folia Morphol 2015; 74, 4: 479-485)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The thickening of the inter-alveolar septa was probably dueto According to morphometry in thein vivo and ex vivo studies, the average thickness of the inter-alveolar septa was 0.05 ± 0.02 mm and 0.03 ± 0.01 mm, respectively. The average thickness of the inter-alveolar septa in the control group was 0.015 ± 0.05 mm, which is consistent with the literature data [47,48]. The total lung capacity of the rat was about 10 mL compared to about 1 mL of the mouse and 6000 mL of a human [49].…”
Section: Resultssupporting
confidence: 90%
“…The thickening of the inter-alveolar septa was probably dueto According to morphometry in thein vivo and ex vivo studies, the average thickness of the inter-alveolar septa was 0.05 ± 0.02 mm and 0.03 ± 0.01 mm, respectively. The average thickness of the inter-alveolar septa in the control group was 0.015 ± 0.05 mm, which is consistent with the literature data [47,48]. The total lung capacity of the rat was about 10 mL compared to about 1 mL of the mouse and 6000 mL of a human [49].…”
Section: Resultssupporting
confidence: 90%
“…In addition to maternal factors transmitted during lactation that may influence lung development, the role of maternal obesity (346) and maternal nutrition during lactation in lung development has also been addressed. In a study on maternal protein restriction, where nursing rats were provided with either a 20% protein diet (control) or a 6% protein diet (protein restriction diet) (153), maternal protein restriction resulted in a pronounced decrease in body mass and lung mass. The authors also reported a persistent (up to 2 mo of postnatal life) decrease in alveolus density and alveolar septal wall thickness and cite lung stereology literature for the method employed (402).…”
Section: L1106mentioning
confidence: 99%
“…During organogenesis, environmental insults may cause discrete structural defects that permanently reduce the functional capacity of an organ. The effects of MPM on offspring organ structure alterations include: less kidney microvascular development, 69 fewer nephrons in the kidney, 70 fewer pancreatic β cells, 71 fewer brain capillaries, 72 fewer neurons that control appetite in the hypothalamus, 73 delay in lung development 74 and altered cellular ratio of liver cell types 75 . Further, MPM affects offspring organ function, including by inducing impaired glucose tolerance, 76 peripheral insulin resistance, 77 coronary disease 78 and hypertension 79 …”
Section: Fetal Programming and Developmental Plasticitymentioning
confidence: 99%